Evolution of Hand Gesture Recognition : A Review (International Journal of Engineering and Computer Science, 2015)
Hand gesture recognition has proven to be an excellent means of Human Computer Interaction over other approaches through keyboards and mouse. This paper presents a review of the evolution of this excellent, easy and natural way of Human Machine Interaction. In this review article the advantages and disadvantages of various techniques that have come up with time and ongoing researches in this field have been discussed. Most of the researchers initially used gloves for the interaction, and then came the vision based hand gesture recognition for 2D graphical interface which uses colour extraction through optical flow and feature point extraction of the hand image captured. New ideas and algorithms have come for 3D applications for moving machine parts or humans. This evolution has resulted in developing a low cost interface device for interacting with objects in virtual environment using hand gestures. Finally, the future work that can be done in this field is also discussed.